Undetectable serum lithium concentrations after coadministration of liquid lithium citrate and apple juice: A case report - Sundus Awan, PharmD; Audrey Abelleira, PharmD, BCPS; Loveleen Khehra, MD; Robin Hieber, PharmD, BCPP (American Association of Psychiatric Pharmacists, 2021)
Lithium is a mood-stabilizing medication approved by the FDA for the treatment of acute manic or mixed episodes of bipolar disorder as well as maintenance treatment. Lithium citrate is an oral solution, and the carbonate salt is available as oral capsules or extended-release tablets. A patient with a psychiatric history of PTSD and schizoaffective disorder-bipolar type, maintained on lithium and olanzapine prior to admission, was admitted to an inpatient psychiatric unit due to destabilization, paranoia, and mania. He was started on lithium citrate, administered with apple juice, while admitted due to nonadherence. An initial serum lithium concentration was found to be undetectable. Lithium was then administered with an alternative non-apple juice liquid, at which point serum lithium concentration became detectable and patient clinically improved. Lithium concentrations may be impacted by a number of causes, such as underlying medical conditions, drug interactions, and diet. As the majority of these factors remained stable during the patient's admission and the serum lithium concentration became detectable after switching from apple juice to an alternative non-apple juice liquid, it led to the identification of a possible incompatibility.